2015
DOI: 10.1109/tnsre.2014.2365834
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of a Low-Cost Noninvasive Hybrid Interface Based on EEG and Eye Movement

Abstract: This paper describes a low-cost noninvasive brain-computer interface (BCI) hybridized with eye tracking. It also discusses its feasibility through a Fitts' law-based quantitative evaluation method. Noninvasive BCI has recently received a lot of attention. To bring the BCI applications into real life, user-friendly and easily portable devices need to be provided. In this work, as an approach to realize a real-world BCI, electroencephalograph (EEG)-based BCI combined with eye tracking is investigated. The two in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 33 publications
1
27
0
1
Order By: Relevance
“…Generally, the application of this composite method has found that it is able to track the user behavioral patterns (29,30). Therefore, it can systematically establish a regular operational routine during which the worker can be reminded remotely if they omit any safety concern.…”
Section: The Feasibility Of Application Of Eeg Mouse Tracking and Ementioning
confidence: 99%
“…Generally, the application of this composite method has found that it is able to track the user behavioral patterns (29,30). Therefore, it can systematically establish a regular operational routine during which the worker can be reminded remotely if they omit any safety concern.…”
Section: The Feasibility Of Application Of Eeg Mouse Tracking and Ementioning
confidence: 99%
“…Los ETs aprovechan una de las escasas habilidades residuales de los casos más graves de la PC: el movimiento de los ojos (Borgestig, Sandqvist, Parsons, Falkmer, & Hemmingsson, 2016). Se han desarrollado otras tecnologías para el acceso al ordenador basadas en electro-oculografía (Úbeda, Iáñez, & Azorín, 2011) (Himabundu, Vivekanandan, Sourabh, & Emmanuel, 2011), electro-encefalografía (Kim, Kim, & Jo, 2015), o movimientos de la cabeza (Raya, Roa, Rocon, Ceres, & Pons, 2010). También hay investigaciones para mejorar el clic, algunas de ellas sobre la base de la electromiografía de superficie (Chin, Barreto, Cremades, & Adjouadi, 2008) (Navallas, Ariz, Villanueva, San Agustín, & Cabeza, 2011).…”
Section: La Parálisis Cerebral Y Los Sistemas De Comunicación Aumentaunclassified
“…This method appears to have high sensitivity and specificity for the diagnosis of CP [15,16]. Motion sensing, by means of MEMS inertial sensors a real scientific breakthrough in the medical field, where there is a need for small ambulatory sensor systems for measuring the kinematics of body segments [17]. As a result, inertial sensors have been chosen for different applications focused on people with motor disorders, such as the evaluation of clinical spasticity assessment (by measuring the range of motion) [18] and the quantification of standing balance by assessing displacement of the center of mass in CP [19] and clinical assessment of tremor in Parkinson [20].…”
Section: Assessment Of Cerebral Palsymentioning
confidence: 99%